The Aims and Objectives of Imam Husain‘s (Peace be Upon Him) Uprising, in the Words of Imam Husain (A. A) Himself - Syed Shuhab Uddin Shah; Naeem Hussain Chang; Imran Khan (Journal of Religion and Society, 2025)
Imam Husain (peace be upon him) belongs to the blessed household of the Messenger of Allah. According to the Qur’an, and the verse of Mubahala, the family of the Prophet are alive in status. Verses of the Qur’an testify to their purity, truthfulness, love and greatness, and many authentic hadiths and books mention their virtues. According to noble hadith, Hasan and Husain are the leaders of the youth of Paradis. Their entire lives were lived according to the Qur’an and in accordance with the character (Seerah) of the Prophet (peace be upon him). Imam Husain spent his blessed childhood in the company of his grandfather, the Messenger of Allah, his father Ali al-Murtaza, and his mother Fatima al-Zahra (peace be upon them all). For about eleven years (11 years) he lived under the care of the Prophet (peace be upon him); for about forty years (40 years) under the guardianship of his father Ali (peace be upon him), and for about ten years (10 years) under the leadership of his brother Hasan al-Mujtaba (peace be upon him), who was the leader of the youth of Paradise. After that, for nearly eleven years (11 years), the period of his Imamate and guidance of the Ummah continued. During this time, Yazid ibn Mu‘awiyah was appointed as ruler over the Ummah. He demanded allegiance (bay‘ah), but Imam Husayn refused. The people of Kufa continuously wrote letters to Imam Husayn, requesting him to come. Imam did not accept the government of Yazid because his purpose was to uphold amr bil-ma‘ruf wa-nahy ‘anil munkar (enjoining good and forbidding evil). Following the path of the Prophet and of Ali (peace be upon them), he set out toward Kufa . Upon reaching Karbala, Yazid’s appointed governor and commander, ‘Umar bin Sa‘ad, confronted Imam with his army. On the day of 10th Muharram, Imam Husain (peace be upon him) was martyred. His sermons, speeches, and the purpose of his struggle give witness to the truth of his martyrdom and his mission. Keywords: Imam Husain (AS), Ahl al-Bayt, Martyrdom, Islamic Leadership, Seerah of Prophet Muhammad (PBUH), Qur'anic Purity, Hadith of Youth of Paradise, Islamic Resistance, Spiritual Legacy.